Engineering of episomal plasmid structure to enhance non-viral Poly(beta-amino ester) nanoparticle gene delivery to liver and brain cancer cells - Joanna Yang; Jack Kollings; Ethan Idnani; David R. Wilson; Isabella G. Cozzone; Shanelle Mendes; Mahita Varanasi; Stephany Y. Tzeng; Jordan J. Green (PLoS ONE, 2026)
The objective of this study was to create and evaluate episomal plasmids for use in non-viral polymeric gene delivery to cancer cells. A comparative analysis was conducted utilizing poly(beta-amino ester)s (PBAEs) as the nanocarrier vector and various hepatocellular carcinoma (HCC) and brain cancer cell lines. A total of fourteen reporter plasmids that varied in promoter (CMV, CAG, EF1α), backbone (Z1, pUNO1, Nanoplasmid [NanoP]), length (~2000 to ~7000 base-pairs), and antibiotic selection marker (Kanamycin, Zeocin, Blasticidin, or none) were constructed, characterized, and evaluated for gene delivery performance. GFP and mCherry plasmids were evaluated in six HCC lines: human (Hep3B), murine (Hepa1–6, Hepa1c1c7), and porcine (A92, A272, B239). Luciferase plasmid constructs were evaluated in three brain cancer lines: murine glioma (CT-2A), human astrocytoma (CCF-STTG1), and human meningioma (IOMM-Lee). When comparing promoters within the same backbone (Z1), the GFP nanoparticles (NPs) under control of a CMV promoter demonstrated consistently higher expression than those with a CAG or EF1α promoter. As EF1α promoters are often used for in vivo applications due to their resistance to gene silencing, four GFP plasmids under control of the EF1α promoter were also compared: Z1-EF1α-GFP, pUNO1-GFP, pUNO1-GFP-SV40, and NanoP-GFP. Of these, the NPs delivering NanoP-GFP, a minimal plasmid, resulted in the highest %GFP+ cells in five HCC cell lines, the highest GFP geometric mean fluorescence intensity (gMFI) in all six HCC cell lines, and the highest luciferase signal in two out of three brain cancer cell lines. NanoP was also the only plasmid evaluated without an antibiotic resistance gene, which may be advantageous when selecting a plasmid best able to meet regulatory guidance for clinical translation. Finally, a modest negative correlation between plasmid size and either transfection efficacy or GFP gMFI was observed. Overall, this work helps to inform episomal plasmid design strategy for use with non-viral gene therapies.